The patent rights of pharmaceutical products and death: between economic balance and human rights - Suryahartati, Dwi; Windarto, Windarto; Nuriyatman, Eko; Kadir, Nor Aida binti Ab (Legality : Jurnal Ilmiah Hukum, 2024)
This study further highlights the relevancy between patent rights and human rights. The impact of the availability and accessibility of essential medicines necessary for Public Health is significant. This study primarily aims to analyze and examine the relationship of patent rights on medicines and pharmaceutical products with human rights and to criticize and evaluate whether the Indonesian government has a policy configuration in the field of essential drugs and the pharmaceutical industry following the principles that support human rights. This research employed qualitative and normative-juridical methods supported by conceptual, statutory, and legal political approaches. Using the theories of legal objectives, utility, and justice, this research focuses on understanding economic law and human rights.  Through in-depth analysis, this study highlights how the patent system for drugs and pharmaceutical products encourages innovation and faces criticism due to limited access for economically vulnerable groups. Hence, the right to health is hampered while the state is responsible for universal access to affordable health care.   The findings of the study indicate that the Patent Rights on drugs and pharmaceutical products are exclusive rights that intersect with human rights in the drug patent system. Several parameters can be used to examine the relationship between human rights and intellectual property. It is necessary to reform the drug patent system to protect the balance and human rights. The findings contribute to a complex understanding of the relevance of patents to human rights while providing a basis for inclusive and sustainable policy development in the global health domain.